Virtual reality training to enhance clinical competence and student engagement in Ghana. - Baidoo, Kodjo; Adu, Chioma (British Journal of Midwifery, 2025)
Background/Aims: Virtual reality simulates real-world scenarios, allowing midwifery students to hone their skills without the risks of live clinical settings. This study's aims were to evaluate the educational impact of virtual reality, including its potential benefits and challenges, in a laboratory at a health education institution in Ghana. Methods: This mixed-methods study examined the implementation of virtual reality in midwifery education. The quantitative arm involved pre- and post-tests administered to two cohorts of first-year midwifery students in consecutive years. The first cohort (n=42 students) was taught using conventional task trainers. The second (n=46 students) was trained using immersive virtual reality simulations. Results: Post-test and practical scores for the virtual reality trained cohort were significantly higher than their traditionally trained counterparts (P<0.0001). These students also reported significantly higher satisfaction (P<0.0001), perceived effectiveness of the course (P<0.0001) and confidence in clinical application (P<0.0001). Conclusions: Virtual reality can substantially enrich the learning environment and enhance the acquisition of practical skills in midwifery education. This investigation into the use of advanced simulation technologies in healthcare education paves the way for future studies on sustainable pedagogical practices. Implications for practice: Virtual reality should be integrated into midwifery curricula, and further research into its long-term educational outcomes and integration strategies is vital.